AI Based Criting E-Modul as a Learning Innovation for Digital and Critical Thinking Literacy: Its Relevance to Transformative Counseling - Maya Masyita Suherman; Ardian Renata Manuardi; Wiwin Yuliani (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2025)
The integration of digital and critical thinking skills is crucial in 21st-century education and counseling. Transformative counseling, which aims to facilitate profound change through critical self-reflection, requires innovative media to achieve its goals. The AI-Based CRITING E-Modul was developed to enhance these competencies, but its conceptual alignment with transformative counseling principles needed systematic validation. Objective: This study aimed to analyze and prioritize the relevance of the CRITING E-Modul's components to the core principles of transformative counseling using the Analytic Hierarchy Process (AHP). Methods: This evaluative study involved five experts in transformative counseling and educational technology. Through pairwise comparison questionnaires, experts judged the relative importance of four main criteria: Critical Reflection, Self-Direction, Disorienting Dilemma, and Contextualization. Results: The AHP analysis revealed that Critical Reflection (weight: 0.415) was the most significant principle, followed by Self-Direction (0.285), Disorienting Dilemma (0.185), and Contextualization (0.115). All consistency ratios (CR < 0.1) indicated acceptable judgment consistency. Conclusions: The AHP method provides a robust framework for validating the relevance of an educational innovation to a theoretical counseling paradigm. The CRITING E-Modul is deemed highly relevant to transformative counseling, primarily through its mechanism of stimulating critical reflection via AI-generated feedback, offering a structured medium for clients or counselor trainees to engage in critical self-examination and cognitive restructuring. This Study provides both a methodological framework and practical guidance for integrating AI tools in counseling context.